Reforming higher education through student-centered learning (SCL) at Universiti Putra Malaysia: lecturers' perspectives - Abu Bakar, Kamariah; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Lope Pihie, Zaidatol Akmaliah (2012)
Malaysian Ministry of Higher Education (MOHE) embarked on reforming higher education in order to produce quality human capital through student-centered learning (SCL) initiatives. In line with this, Universiti Putra Malaysia (UPM) had set out to train her academic staff starting from 2004. With the training, the question arises as to whether the lecturers are able to translate the newly acquired knowledge and skills into classroom practices. This study aimed to explore the types of teaching methods used and the extent of use as perceived by the lecturers. Apart from that, the study also aimed to explore how competent the lecturers were in terms of their chosen teaching methods. Nine hundred and one lecturers participated in this study. The collected baseline data showed lecturers perceived themselves to be generally practicing SCL approaches in their classes. The results also suggested that the lecturers perceived themselves to be competent in conducting the SCL approaches such as the Student Class Presentation, Group Discussion, Group Project, Interactive Lectures, Tutorials and Individual Project. In terms of assessment, they tend to use conventional approaches.